Cryptoreality A Conversation with Artur Ekert. - Burton, Howard (Ideas Roadshow Conversations Ser., 2021)
This book is based on an in-depth filmed conversation between Howard Burton and Artur Ekert, Professor of Quantum Physics at the Mathematical Institute at the University of Oxford and Director of the Centre for Quantum Technologies and Lee Kong Chian Centennial Professor at the National University of Singapore. Artur Ekert is one of the pioneers of quantum cryptography. This wide-ranging conversation provides detailed insights into his groundbreaking research and covers many fascinating topics such as mathematical and physical intuition, a detailed history of cryptography from antiquity to the.